How does student learn mathematics through traditional food? (a hypothetical learning trajectory) - Tarida, Luthfiana; Anjarsari, Elly; Hasan, Buaddin; Widayati, Farida Esti (Unnes Journal of Mathematics Education, 2023)
This study aimed to design a hypothetical learning trajectory for a two-dimensional figure area (quadrilateral and triangle) using the geometric shape of traditional food, tempe mendoan as a learning context. This research was qualitative research with data collection methods using literature studies, interviews, and documentation. The subjects in this study were seventh-grade junior high school students in SMP IT Nurul Fikri Bogor. The results of this study are in the form of a hypothetical learning trajectory design in learning the two-dimensional figure area through exploration of Banyumas food tempe mendoan, students measure each side of the rectangle from the shape of tempe mendoan, students divide the rectangle into square units as many as the results of each measurement side, students counts the number of unit squares that cover the rectangular area, the student finds the formula for the area of ​​a square and a rectangle. Next, students divide one rectangle into two right triangles of equal size, students find the formula for the area of ​​a triangle. Students attach the triangles to the provided two-dimensional figure shapes, students record the number of right triangles needed to cover each shape and find these relationships so that students can find area formulas for other shapes such as parallelograms, trapezoids, and rhombuses.